THE INFLUENCE OF INFLATION, EXCHANGE RATE AND INTEREST RATE, ON STOCK PRICE - Octavia, Evi (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: This study aims to determine the effect of inflation, exchange rates and interest rates on stock prices. Design / methodology / approach: The data used in this study is panel data, which is a combination of time series data and cross sections. The sample data of 11 companies were taken from the cross section unit data and time series data for the 2016-2019 period. The analytical method used in this study is the multiple regression analysis model. Findings: The results show that inflation, interest rates and exchange rate fluctuations will influence the consumers and the world economy, because they will create inefficiencies and distort prices. High inflation and interest rates will cause company sales to decrease and capital costs to rise, so company profits will decline which will have an impact on the company’s stock price. High inflation and interest rates will also affect the decline in a country’s exchange rate. In the condition of a country with a high inflation rate, this export-oriented company will benefit from an increase in sales value. Conversely for importing companies, changes in exchange rates will cause an increase in production costs, consequently the company’s profits will decrease which will cause a decline in share prices and increased losses suffered due to differences in exchange rates between countries. Practical implications: This research is expected to be useful for managers in making decisions Originality / value: this study different from previous studies because it examines the simultaneous effect of inflation, exchange rates and interest rates on stock prices.